From Idol Affinity to Market Virality: LALISA's Parasocial Authority and LABUBU's Global Adoption - Alan Munandar; Novianah Dwi Pratiwi; Nanda Putri Adilah; Rachel Indah Permatasari (Reslaj: Religion Education Social Laa Roiba Journal, 2026)
Communication study still has not looked at the connection between celebrity parasocial authority and the spread of viral products. When Thai K-pop star LALISA (Lalisa Manobal of BLACKPINK) officially sponsored Pop Mart's LABUBU collectibles in April 2024, sales throughout the world went up by 250% and sales in the U.S. went up by 1,200% year over year. This phenomena demonstrates how parasocial relationships may affect consumer behavior across geographic and demographic lines. This quick overview of the literature looks at how parasocial authority between celebrities and their fans leads to viral product adoption in online stores. We found peer-reviewed articles on parasocial interaction, celebrity credibility, viral marketing, and product adoption by searching Scopus, Web of Science, and Communication & Mass Media Complete. The findings were divided into groups based on processes and consequences and then put together in a story. The results show that parasocial authority may predict purchase intention and brand loyalty via social influence, aspirational identification, and trust-based persuasion. However, these effects are stronger when fandom intensity and cultural closeness are taken into account. The growth of K-pop has made intentional parasocial relationships even stronger. This shows that celebrity parasocial authority is a different way to persuade people than traditional endorsements. These results have important effects on how we understand influencer marketing and how people act in viral situations in digital culture. They show how parasocial ties may be used strategically to get people throughout the world to interact with products.